Sistem Pendukung Keputusan Pemilihan Distributor Terbaik Menggunakan Metode TOPSIS dan Pembobotan ROC - Kesuma, Febriza Puja; Rusliyawati, Rusliyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Distributors are important intermediaries in the supply chain to distribute products from producers to retailers or to end consumers. The best distributors are strategic partners who play a vital role in the success of the supply chain and marketing of products. The main problem in choosing the best distributor often revolves around several critical factors. The best distributors must have a commitment to innovation in the distribution process and continuous improvement to improve efficiency, reduce costs, and meet the challenges of the ever-changing market. The purpose of this study is to develop and implement a decision support system for the selection of the best distributor using the TOPSIS method and ROC weighting, to assist companies in identifying and selecting the distributor that is most in accordance with the criteria that have been set. The ROC method is based on a ranking of criteria given by decision-makers. The results of the ranking of the best distributor selection show that the first best distributor with a final score of 0.72949 was obtained by Garuda Food, the second best distributor with a final score of 0.64131 was obtained by Wings Food, and the third best distributor with a final score of 0.61099 was obtained by Toko Lucky. The results of this ranking are the basis for optimizing its distribution network for the company. By choosing distributors that have the highest ratings, companies can ensure that their products reach customers with the highest quality and on time. These rankings not only assist companies in making strategic decisions but also drive quality and efficiency improvements throughout the supply chain.